2012
DOI: 10.1159/000342391
|View full text |Cite
|
Sign up to set email alerts
|

Is Primary Pulmonary Meningioma a Giant Form of a Meningothelial-Like Nodule?A Case Report and Review of the Literature

Abstract: Minute pulmonary meningothelial-like nodules (PMNs) are asymptomatic, small nodules that are occasionally detected in surgical or autopsy specimens. Recent improvements in tumor imaging and the increased use of computed tomography (CT) scans of the chest have led to the early detection of these pulmonary nodules in various clinical settings, often before surgery or health examinations. However, large PMNs have rarely been observed. In this study, we report a patient with a large PMN, which was almost identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…It has been reported to originate from ectopic embryonic residual arachnoid or multifunctional mesenchymal cells . Some authors have suggested that PPM may originate from minute meningothelial‐like nodules in the lungs . This lesion has been listed in the World Health Organization histological classification of lung and pleural tumors since 1999; however, its precise origin remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to originate from ectopic embryonic residual arachnoid or multifunctional mesenchymal cells . Some authors have suggested that PPM may originate from minute meningothelial‐like nodules in the lungs . This lesion has been listed in the World Health Organization histological classification of lung and pleural tumors since 1999; however, its precise origin remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis of such tumors, at least when they grow from meninges, is unfavorable with high rates of recurrence and metastases. 14,17,25 Although the PPM in the present case was focally rhabdoid-looking, it lacked other features, which could undoubtedly categorize this tumor as WHO grade III: in general tumor was well-differentiated, and mitotic activity was low. A recent study 26 analyzed the behavior and prognosis of 44 rhabdoid CNS meningiomas lacking other histological features of malignancy.…”
Section: Discussionmentioning
confidence: 65%
“…[ 8 ] Previous reports of primary pulmonary meningioma with contrast-enhanced CT images showed various enhancement patterns, such as heterogeneous or nodular enhancement, [ 12 , 13 ] poor enhancement, [ 14 , 15 ] or homogeneous enhancement. [ 2 , 16 , 17 ]…”
Section: Discussionmentioning
confidence: 99%